My[Sacred]Space: Discovering Sacred Space in Cyberspace. - Walker, Seth (Journal of Religion & Popular Culture)
The notion of "sacred space" has received attention from various scholars in the field of religious studies, as well as other academic disciplines. However, twentieth century contributions are specifically relevant to the study at hand. Moreover, it seems only natural to begin an analysis of "sacred space" by describing what is meant by the word "sacred" in its territorial connection with "space." Therefore, specific understandings of "the sacred" will be explored, such as those developed by French sociologist Émile Durkheim and French historian of religion Mircea Eliade. Following this, the modern construct "cyberspace" will be explored, as the reader is led into the main topic under investigation: the existence of sacred space in cyberspace, with a special emphasis on the cyber-social network MySpace. This part of the investigation will explore the various correlations that exist between these understandings of "sacred space" and those found in MySpace, arguing that the latter qualifies as being analogous to the former by the way in which it functions for its users.